2022
DOI: 10.1002/erv.2913
|View full text |Cite
|
Sign up to set email alerts
|

Family‐reported barriers and predictors of short‐term attendance in a multidisciplinary intervention for managing childhood obesity: A psycho‐family‐system based randomised controlled trial (ENTREN‐F)

Abstract: This study was aimed to examine patient enrolment in the preintervention stage, family-reported barriers, attendance rates and underlying predictors of short-term attendance in a family-system-based randomised controlled trial for managing childhood obesity in children aged 8-12-yearsold (ENTREN-F). Method: Psychosocial and anthropometric measures were collected through primary health referral. The data were used for descriptive analyses of sample characteristics and linear regression analyses.Results: Low enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Adolescents were encourage to bring a friend to [one] session, and friends were integrated into the activities [ 71 ] [ 29 , 33 , 35 40 , 42 , 43 , 47 , 49 , 50 , 56 , 60 63 , 70 72 ] The Youth Quality of Life (YQOL) Inventory, including a social relationship subscale [ 49 ] The Support for Exercise Scale (revised version) [ 56 ] The Social Support for Eating Habits and Exercise Scale [ 61 ] Parent Relationship with Peer Group Scale [ 33 ] Family Functioning Family member roles and interactions that affect day-to-day living within the home environment, including acceptance and understanding of one another, family decision-making and problem-solving processes, and general communication among family members. Simply described as the overall healthiness of a family unit 10 Multidisciplinary FBBT : Nutrition-related topics and systemic interventions to facilitate family functioning by reinforcing family resources and improving the emotional climate for adolescents with obesity [ 57 ] [ 30 , 31 , 33 , 35 40 , 47 , 56 , 57 , 60 , 64 , 70 72 ] The Self-Report Family Inventory (SFI), including the conflict resolution, cohesion, and family nurturance subscales [ 60 ] The Family Adaptability and Cohesion Evaluation Scales IV (FACES IV) [ 67 , 68 ] The Family Climate Scale [ 72 ] Family Questionnaire (FQ) [ …”
Section: Resultsmentioning
confidence: 99%
“…Adolescents were encourage to bring a friend to [one] session, and friends were integrated into the activities [ 71 ] [ 29 , 33 , 35 40 , 42 , 43 , 47 , 49 , 50 , 56 , 60 63 , 70 72 ] The Youth Quality of Life (YQOL) Inventory, including a social relationship subscale [ 49 ] The Support for Exercise Scale (revised version) [ 56 ] The Social Support for Eating Habits and Exercise Scale [ 61 ] Parent Relationship with Peer Group Scale [ 33 ] Family Functioning Family member roles and interactions that affect day-to-day living within the home environment, including acceptance and understanding of one another, family decision-making and problem-solving processes, and general communication among family members. Simply described as the overall healthiness of a family unit 10 Multidisciplinary FBBT : Nutrition-related topics and systemic interventions to facilitate family functioning by reinforcing family resources and improving the emotional climate for adolescents with obesity [ 57 ] [ 30 , 31 , 33 , 35 40 , 47 , 56 , 57 , 60 , 64 , 70 72 ] The Self-Report Family Inventory (SFI), including the conflict resolution, cohesion, and family nurturance subscales [ 60 ] The Family Adaptability and Cohesion Evaluation Scales IV (FACES IV) [ 67 , 68 ] The Family Climate Scale [ 72 ] Family Questionnaire (FQ) [ …”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we observed a non-significant inverse relationship between duration of the intervention and BMI-SDS at baseline ( p = 0.07), suggesting that additional studies are needed in order to clarify the relationship between BMI-SDS and adherence. Parental factors can also be important determinants for the child’s adherence, since several earlier studies have suggested that children from families with low socioeconomic status or obesity were associated with lower adherence to an intervention [ 31 , 30 ]. However, results from the present study were unable to confirm these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Limited knowledge exists on why children and their families often prematurely leave a lifestyle intervention targeting childhood obesity [ 22 , 27 31 ]. However, low socioeconomic status [ 29 ], lower parental educational level [ 30 , 31 ], higher degree of obesity [ 27 , 28 , 31 ], and higher age of the participating child [ 26 , 29 ] at treatment onset have all been reported to increase the risk of drop-out.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even if therapy prevails, this can be impeded in the presence of undetected or untreated parental depression that may not be a treatment focus. 38,39 As well, some attention to the allied role of persistent or distressing stressful life events in childhood or even before the child is born, 40 as well as apparent increases in parental and teacher depression post COVID, 41 may need to be acknowledged to a higher degree in the future to avert any increasingly marked feelings of distress and their negative consequences, including stigmatization and emotional eating among vulnerable youth and their mothers. 42 Unfortunately, although childhood obesity or overweight has been identified as a significant attribute for more than a decade, 33,34 and the COVID-19 pandemic clearly compounded the overall health opportunities for youth, it is clear a much more concerted effort in multiple spheres is imperative in order to successfully avert both the onset of childhood obesity, as well as depression, and their bidirectional association, that could provoke life-long incurable health and social challenges.…”
Section: Summary and Discussionmentioning
confidence: 99%